SERS detection of radiation injury biomarkers in mouse serum. Issue 10 (29th January 2018) - Li, Liansheng; Xiao, Rui; Wang, Qi; Rong, Zhen; Zhang, Xueqing; Zhou, Pingkun; Fu, Hanjiang; Wang, Shengqi; Wang, Zhidong
Abstract : A rapid and on-site detection method would be needed to triage of casualties and proper medical treatment in a large scale radiological catastrophe. The detection method of SERS would be a effective approach. Abstract : In a large-scale radiological catastrophe, it is expected that hundreds and thousands of people could be exposed to radiation. A rapid method is required for triage of casualties to determine proper medical treatment. In this article, mice were exposed to different radiation doses and sera of mice were investigated by surface-enhanced Raman spectroscopy (SERS) and orthogonal projections to latent structure discriminant analysis (OPLS-DA) after total body irradiation (TBI). The results of the present study indicated that differences have widened over time. The different radiation groups showed a slight overlap at 24 h and 72 h but were completely distinct at the 10th day after TBI. The SERS spectrum between the normal group and the irradiated group showed a significant difference at 24 hours. The same trend was depicted in scatting score plots. Significant differences in Raman peaks were found, such as 744 and 1495 cm −1 corresponding to riboflavin and 593 and 1204 cm −1 corresponding tol -tryptophan. The lack of riboflavin andl- tryptophan will influence metabolism levels. Above all, these results bear potential in the development of label-free and rapid tools for on-site detection and screening of irradiation injuries.